2021
DOI: 10.22306/al.v8i2.208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Principles of Reverse Logistics in Waste Management

Abstract: The goal of mentioned contribution is to moderate the unwanted effects of economics on environment in the form of more purposed economy with material sources from recycling, collection, separation and processing of returnable products. It is a global trend nowadays to lower waste production and to minimize effects on the environment. We are going to deal with effectiveness of partly underground containers in Slovakia and new trends about possibilities of other uses of PET bottles. The article deals with the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…As a result, there is a link between economic motivation and solid waste management in this case. From the results of this survey, reverse logistics and solid waste management contribute to economic growth and improved company performance, and this finding is consistent with the findings [58,59] that show recycling efficiency has a positive impact on economic performance. Economic reasons, marketing aims, and company objectives are among the value drivers from this perspective.…”
supporting
confidence: 90%
“…As a result, there is a link between economic motivation and solid waste management in this case. From the results of this survey, reverse logistics and solid waste management contribute to economic growth and improved company performance, and this finding is consistent with the findings [58,59] that show recycling efficiency has a positive impact on economic performance. Economic reasons, marketing aims, and company objectives are among the value drivers from this perspective.…”
supporting
confidence: 90%
“…This work is structured as follows: Section 1 briefly reviews the state-of-the-art from the related topics of this research, that is, waste collection and management status, syngas Energies 2023, 16, 7384 2 of 18 and biodiesel past utilizations and prospects for the future, use of biofuels in ICE, data of raw materials proximate and ultimate analysis, reference values for hydrogen percentage in volume of syngas from other materials, and, conclusively, the general advances in WtE in regions such as Europe and Latin America. Section 2 provides a methodology explanation about the gasification unit and the engine bench setup, and the calculation involved in the thermochemical process.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Figure 2 shows a flowchart of waste management from collection to final energy use. Regarding the collection of waste, several studies have shown the importance of logistic planning as well as effective selective collection [15,16]. Some materials found in municipal waste can either be recycled or sorted for energy recovery to be utilized in RDF or biofuels, as in the case of biodiesel produced from WCO [17].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…However, an important element in waste management are urban areas, which have to cope with a significant amount of waste generated by city dwellers , Zajac et al 2019a, Zajac et al 2020, Zatrochova et al 2020). The waste generated in this way should be collected and transported (Izdebski & Jacyna 2018), with minimized amount of partially filled transports (Wozniak et al 2016, Wozniak et al 2018) and an environmentally friendly transport system (Jacyna et al 2018) in the scope of the implemented concept of sustainable transport (Chamier-Gliszczyński 2011, Chamier-Gliszczyński & Bohdal 2016, Chamier-Gliszczynski 2016a.…”
Section: Introductionmentioning
confidence: 99%